The Cognitive-Semantic Approach As A Methodological Basis For The Study Of Foregrounding Tools (Eurasian Scientific Herald, 2023)
The article contains opinions on the feature of foregrounding, as a tools for cognitive semantics, ongoing research’s held for the readers to send or accept information, the implementation of stylistic methods of accepting the world or fasten cognitive ability